Stability Analysis of Three Phase Induction Motor Drive Using Different Stability Criteria - M. S. Alam (International Journal of Advanced Science and Technology, 2020)
In this paper stability analysis of three phase induction motor drive is carried out using different stability criteria of control system. The mathematical model of motor is described by different differential equations. One of the major goal of this paper is to derive the mathematical equations of motor by describing the dynamics of the drive under sudden change of load. This model is developed in direct-quadrature axes using two phase motor. The mathematical equations which are developed with the help of this model are non-linear in nature. With the help of perturbation technique, these equations are linearized around an operating point. Based on different input-output combinations a number of transfer functions are obtained. In this paper the transfer function between Te (proportional to ωr) and ωs is developed and the stability analysis is carried out using this transfer function. MATLAB codes are used to carryout this analysis.